Tunda Island as a Marine Tourism Destination - Iman Mukroman; Ronny Yudhi Septa Priana; Asri Sulistian (Journal Hotspot, 2021)
This study was conducted to determine the Tunda Island as a maritime tourism destination. It was reviewed by using SWOT analysis. This study uses qualitative research methods with data collection techniques such as interviews, observation, documentation studies, and focus group discussion. Results of research conducted shows that the Island Tunda as a maritime tourist attraction has the power in the form of underwater beauty. Besides, it also has a big opportunity in terms of strategic location and not far from the center city. But Tunda Island has several weaknesses in the form of human resource and low tourism awareness, as well as waste problem. The challenges faced by Tunda Island is the preservation of underwater parks that can be threatened when many tourists who come and tourism activities.